Haneke avec Foucault: the White Ribbon, Religion, and Violence - Herling, Bradley L. (The journal of religion and film, 2021)
This article utilizes Michel Foucault's characterization of the Christian pastorate to examine The White Ribbon (2009), directed by Michael Haneke. Foucault's framework assists us in inspecting the nature of the Protestant community depicted in the film, its systems of discipline, repression, and control, and the bond between these systems and the violence that erupts as the plot unfolds. Reading Haneke avec Foucault thus sheds light on the broader problem of "religious violence," while also drawing out the sometimes submerged but skillful interpretation of religion proposed by these two auteurs.